Women's autonomy in health care decision-making in developing countries: a synthesis of the literature - Osamor PE; Grady C (Dove Medical Press, 2016)
Pauline E Osamor, Christine Grady Department of Bioethics, Clinical Center, National Institutes of Health, Bethesda, MD, USA Abstract: Autonomy is considered essential for decision-making in a range of health care situations, from health care seeking and utilization to choosing among treatment options. Evidence suggests that women in developing or low-income countries often have limited autonomy and control over their health decisions. A review of the published empirical literature to identify definitions and methods used to measure women’s autonomy in developing countries describe the relationship between women’s autonomy and their health care decision-making, and identify sociodemographic factors that influence women’s autonomy and decision-making regarding health care was carried out. An integrated literature review using two databases (PubMed and Scopus) was performed. Inclusion criteria were 1) publication in English; 2) original articles; 3) investigations on women’s decision-making autonomy for health and health care utilization; and 4) developing country context. Seventeen articles met inclusion criteria, including eleven from South Asia, five from Africa, and one from Central Asia. Most studies used a definition of autonomy that included independence for women to make their own choices and decisions. Study methods differed in that many used study-specific measures, while others used a set of standardized questions from their countries’ national health surveys. Most studies examined women’s autonomy in the context of reproductive health, while neglecting other types of health care utilized by women. Several studies found that factors, including age, education, and income, affect women’s health care decision-making autonomy. Gaps in existing literature regarding women’s autonomy and health care utilization include gaps in the areas of health care that have been measured, the influence of sex roles and social support, and the use of qualitative studies to provide context and nuance. Keywords: women’s autonomy, health decision-making, developing country, reproductive health, health care utilization